Homeobox a5 Promotes White Adipose Tissue Browning Through Inhibition of the Tenascin C/Toll-Like Receptor 4/Nuclear Factor Kappa B Inflammatory Signaling in Mice - Cao, Weina; Huang, Hongtao; Xia, Tianyu; Liu, Chenlong; Muhammad, Saeed; Sun, Chao (Frontiers in Immunology, 2018)
Lipopolysaccharides (LPS) induces rapid increases in systemic inflammatory factors. As adipose tissue is a key contributor to the inflammatory response to numerous metabolic stimuli, it is important to understand the mechanism behind the LPS-induced inflammation in white adipose tissue (WAT). Homeobox a5 (Hoxa5) is an important transcription factor, which is highly expressed in adipose tissue, and its mRNA expression is increased at cold exposure in mice. So far, the function of Hoxa5 in adipose tissue browning has been poorly understood. So, the objective of this study was conducted to determine the role of Hoxa5 in adipose inflammatory response as well as white adipose browning in mice. LPS-induced inflammatory and cold-induced browning model were conducted. We compared the coordinated role of Hoxa5 in inflammation and thermogenesis of mice adipose. Transcriptional and methylation regulation was determined by luciferase assay, electrophoretic mobility shift assay (EMSA) and bisulphite conversion experiment. Hoxa5 and Tenascin C (TNC) were involved in WAT inflammation and browning in mice with LPS injection. Furthermore, Hoxa5 inhibited TNC involved activation of TLR4/NFĸB signal pathway and promoted WAT browning. Moreover, We found a BMP4/Smad1 signal, closely related to browning, was activated by Hoxa5. Hoxa5 relieved adipocyte inflammation by decreasing TNC-mediated TLR4 transducer and activator of the NFĸB pathway. Interestingly, descended methylation level increased Hoxa5 expression in cold exposure. Our findings demonstrated that Hoxa5 alleviated inflammation and enhanced browning of adipose tissue via negative control of TNC/TLR4/NFĸB inflammatory signalling and activating BMP4/Smad1 pathway. These our findings indicated a novel potential means for the regulation of inflammation in adipocytes to prevent obesity and other inflammatory diseases.